Rhizoctonia solani fucomannogalactan: Chemical characterization and antiproliferative activity - Alexandre, Samara M.A. [UNESP]; Corradi da Silva, Maria L. [UNESP]; Vasconcelos, Ana F.D. [UNESP]; Exposti, Diego T.D. [UNESP]; Tischer, Cesar A.; Prieto, Alicia; Diaz, Dolores; Kaneno, Ramon [UNESP] (Elsevier, 2018)
A fucomannogalactan from Rhizoctonia solani biomass was obtained after hot aqueous extraction and purified by freeze-thaw cycles and gel filtration chromatography on Sepharose CL-6B. The polysaccharide was homogeneous after HPSEC/RID analysis (Mw/Mn ~ 1.1), displaying an average molecular weight of 15.4 × 103 Da. Its chemical structure was determined by methylation analysis (GC/MS) and spectroscopy (FTIR, 1D and 2D NMR). The polysaccharide had a branched α-1,6-linked Galp backbone with 66% linear residues, a number of which were at O-3 methylated. Side chains (34%) were always linked at O-2 positions of the main chain and consisted of single, non-reducing ends of α-D-Manp (6%) and α-L-Fucp (28%). Analysis of its biological activity showed that the highly purified fucomannogalactan from R. solani inhibited the proliferation of colon cancer cells in vitro, but that it did not have the same activity against lung cancer cells.
Keywords: Antiproliferative activity; Fucomannogalactan; Gel filtration chromatography; NMR spectroscopy; Rhizoctonia solani